Neuroeducation-Based Ice Breaking: A Conceptual Framework for Improving Self-Efficacy in Hybrid Learning Environments - Ahmad Silmul Fuady; Andriansyah Andriansyah; Aqil Munawwar; Abdul Rosit; M. Ismail (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Hybrid learning environments intensify cognitive fragmentation, emotional fatigue, and psychological disconnection by forcing learners to navigate simultaneous digital and physical interaction systems that frequently overload attentional capacity and weaken academic confidence. Such conditions expose a critical gap in contemporary pedagogy, where instructional engagement strategies often ignore the neurobiological mechanisms shaping learner readiness and self-efficacy. This article synthesizes neuroeducation and educational psychology to propose a novel conceptual framework termed the Neuro-Flow Mechanism, designed to explain how neuroeducation-based ice breaking regulates emotional and cognitive states within hybrid classrooms. Employing an integrative literature review approach, the study bridges neuroscientific perspectives on cortisol modulation, dopaminergic activation, oxytocin-mediated social bonding, and prefrontal cortex stabilization with Bandura’s four pillars of self-efficacy: mastery experiences, vicarious experiences, social persuasion, and physiological-emotional states. The analysis demonstrates that strategically designed cognitive priming activities recalibrate emotional safety, reduce split-attention overload, strengthen collaborative trust, and sustain working memory readiness before complex instruction begins. The framework redefines ice breaking from a recreational classroom ritual into a biologically functional pedagogical mechanism capable of constructing brain-safe hybrid learning ecosystems that sustain engagement, resilience, and long-term academic self-efficacy.